The Gravity Model of Indonesian Tourism Trade and Investment - Faurani Santi Singagerda; Andi Desfiandi; Elin R Marantika (ETIKONOMI, 2023)
This study aimed to determine the performance of tourism investment and trade in Indonesia following the outbreak of COVID-19 and other economic and non-economic factors. Goods and services for Indonesian tourism from 8 sample countries over 26 years were examined using a tourism economy approach and a gravity panel model of the flow of investment and trade. Regarding research originality, the model developed is constructing tourism economic theory applying the Keynesian method. The results showed that economic factors, such as GDP per capita, interest rates, exchange rates, prices, and economic distance, and non-economic factors, such as population, travel alerts, and pandemics, significantly affect investment flows and the tourism trade. Furthermore, tourism competitiveness increased globally in 2019. However, potential economic leakage in FDI and trade were identified. As a result, the government must emphasize long-term and efficient investment and trade in the tourism sector, particularly in the context of systemic shocks such as a pandemic.JEL Classification: C58, D58, Z32, Z38How to Cite:Singagerda, F. S., Desfiandi, A., & Marantika, E.R. (2023). The Gravity Model of Indonesian Tourism Trade and Investment. Etikonomi, 22(1), 143–154. https://doi.org/10.15408/etk.v22i1.25222.